2007
DOI: 10.1371/journal.pone.0000840
|View full text |Cite
|
Sign up to set email alerts
|

The Tell-Tale Heart: Population-Based Surveillance Reveals an Association of Rofecoxib and Celecoxib with Myocardial Infarction

Abstract: BackgroundCOX-2 selective inhibitors are associated with myocardial infarction (MI). We sought to determine whether population health monitoring would have revealed the effect of COX-2 inhibitors on population-level patterns of MI.Methodology/Principal FindingsWe conducted a retrospective study of inpatients at two Boston hospitals, from January 1997 to March 2006. There was a population-level rise in the rate of MI that reached 52.0 MI-related hospitalizations per 100,000 (a two standard deviation exceedence)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…One study of such an automated system monitored 36 653 inpatients over an 18-month period and correctly identified 731 ADEs in patients, whereas health professionals only reported 92 (18 ). A study published by one of the authors showed the potential for automated signal detection through population monitoring to detect early signs of COX-2 inhibitor's association with myocardial infarction (21 ). Although there are potential difficulties in translating data entry from physician-based EHRs to accurately detect signals, one study found consistency between natural language processing characterization of patients with asthma with known population characteristics (22 ), providing further validation of this approach.…”
Section: Pharmacovigilance and Adverse Drug Eventsmentioning
confidence: 99%
“…One study of such an automated system monitored 36 653 inpatients over an 18-month period and correctly identified 731 ADEs in patients, whereas health professionals only reported 92 (18 ). A study published by one of the authors showed the potential for automated signal detection through population monitoring to detect early signs of COX-2 inhibitor's association with myocardial infarction (21 ). Although there are potential difficulties in translating data entry from physician-based EHRs to accurately detect signals, one study found consistency between natural language processing characterization of patients with asthma with known population characteristics (22 ), providing further validation of this approach.…”
Section: Pharmacovigilance and Adverse Drug Eventsmentioning
confidence: 99%
“…An increasing body of evidence (Sung et al, 2003;Brownstein et al, 2007;Kahn et al, 2007;Wilke et al, 2007;Seyfried et al, 2009;Kohane, 2011) indicates that data from EDRs for research can have multiple benefits. This study determined which data elements used in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Other industries, such as finance and energy, have embraced data analytics [6], and researchers at Google have shown that an order of magnitude growth in the size of data sets leads to significant improvements in performance of analyses and can overshadow improvements in modeling techniques [7]. Big data have only been reported in a select few epidemiologic studies, such as those linking myocardial infarction and rosiglitazone [8] or rofecoxib [9]. Two significant issues need to be resolved to enable open data mandates: guaranteeing the privacy of study subjects [10] and creating a safe, fair, and open infrastructure for data sharing [4].…”
Section: Open Data: Can It Prevent Research Fraud Promote Reproducibmentioning
confidence: 99%